Developing a cybersecurity culture model among online banking users in Nigeria - Garba, Jamilu (2025)
This research examines the interplay of human factors influencing cybersecurity culture among online banking users in Nigeria and develops a tailored model to address the vulnerabilities inherent in user behavior. The increasing reliance on online banking in Nigeria has amplified the need for robust cybersecurity measures to mitigate the growing threat of cyberattacks. While technological solutions are essential, human factors play a critical role in shaping cybersecurity culture, particularly in developing economies with unique socio-economic challenges. Grounded in the Theory of Planned Behavior (TPB), this study identifies critical constructs such as cybersecurity awareness, education, policy compliance, interpersonal trust, and social norms as determinants of a secure cybersecurity culture. Employing a mixed-methods approach, the qualitative phase involved in-depth interviews with cybersecurity experts to validate the cybersecurity culture model, ensuring its relevance to Nigeria's unique context. The quantitative phase surveyed 392 online banking users, employing Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships among the identified factors. The findings reveal significant associations between cybersecurity culture and constructs such as awareness, education, and policy compliance, while interpersonal trust exhibited no significant influence. This study provides actionable insights for financial institutions, policymakers, and cybersecurity professionals, offering a robust framework to enhance user-centric cybersecurity strategies. The proposed model serves as a practical tool for addressing behavioral vulnerabilities and fostering a proactive cybersecurity culture, ensuring the resilience of Nigeria's online banking sector against ever-evolving threats.